2005
DOI: 10.1039/b508661b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of new oxorhenium and oxotechnetium complexes with XN2S-tetradentate semi-rigid ligands (X = O, S, N)

Abstract: Twelve novel oxo-technetium and oxo-rhenium complexes based on N2S2-, N2SO- or N3S-tetradentate semi-rigid ligands have been synthesised and studied herein. By reacting the ligands with a slight excess of suitable [MO]3+ precursor (ReOCl3(PPh3)2 or [NBu4][99gTcOCl4]), the monoanionic complexes of general formula [MO(Ph-XN2S)]- could be easily produced in high yield. The complexes have been characterized by means of IR, electrospray mass spectrometry, elemental analysis, NMR and conductimetry. The crystal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The semi-rigid XH-diamine-thiol (X = O in 5 and X = S in 6 ) chelators used for our studies were modified from the XH-diamide-thiol chelators reported by Le Gal and coworkers 24. The complexation of [Re(V)O] 3+ with Le Gal’s XH-diamide-thiol chelators led to Re complexes with one negative charge due to the loss of four protons.…”
mentioning
confidence: 99%
“…The semi-rigid XH-diamine-thiol (X = O in 5 and X = S in 6 ) chelators used for our studies were modified from the XH-diamide-thiol chelators reported by Le Gal and coworkers 24. The complexation of [Re(V)O] 3+ with Le Gal’s XH-diamide-thiol chelators led to Re complexes with one negative charge due to the loss of four protons.…”
mentioning
confidence: 99%
“…2.15–2.18 Å) suggesting some degree of multiple bond character. 51 , 56 The Re–N1–N2 and Re–N5–N6 bond angles average 124°, suggesting an approximately sp 2 hybridized nitrogen. The Re–S bond distances average 2.29 Å and are similar to the Re–S bond distances in rhenium(V) complexes with amino thiolate ligands and Re–S bond distances in rhenium complexes with thiosemicarbazonato ligands.…”
Section: Resultsmentioning
confidence: 99%
“…A further complication is that thiol-containing ligands are often air-sensitive and prone to oxidation, and this makes their incorporation into premade radiopharmaceutical kits challenging. The use of semirigid tetradentate ligands, lacking tertiary amines, for complexation with [TcO] 3+ has the advantage of precluding the formation of syn and anti diastereomers. , …”
Section: Resultsmentioning
confidence: 99%
“…Both complexes crystallize in centrosymmetric space groups, with both SP-5-13-C and SP-5-13-A enantiomers present in the unit cell . In [ReO L 1 ], the Re–N1 bond length [1.908(2) Å] is shorter than the Re–N2 bond [1.978(3) Å], but both bonds are shorter than typical Re–N single bonds (approximately 2.13 Å), suggesting some degree of multiple-bond character consistent with deprotonation of the amine and amide, respectively, and consistent with other complexes that feature a Re–N amide bond. , The Re–N pyridine bond in [ReO L 2 ] [2.086(2) Å] is marginally shorter than the Re–N pyridine bond in [ReO L 1 ] [2.130(2) Å], but both are similar to the Re–N pyridine bond length found in [ReO 2 (pyridine) 4 ] + . The Re–O phenolate bond distance is 1.968(2) Å in [ReO L 1 ] and 1.969(2) Å in [ReO L 2 ].…”
Section: Resultsmentioning
confidence: 99%